Enhanced Hybrid Techniques for Data Hiding - kaur, Sukhjeet; Singh, Harpal (International Journal of Computer Sciences and Engineering, 2025)
Security is the occasions of anyone unfastened from hazard. Safety has very crucial difficulty in conversation. To solve the difficulty of security we arrange those integrate techniques. Cryptography is the artwork and science of observe of generating the secret message of the original message. As Steganography is the art and technological know-how of hiding verbal exchange, into some other media type file consisting of image, text and video. The numerous cryptography and steganography methods to cover statistics like LSB, DCT etc. However these strategies are wounded by a few problems like reduce quality of image, lower covering capacity. To success over this difficulty the proposed strategies use Substitution Encryption method to similarly encrypt the data and steganography method uses the Improved LSB Steganography technique which uses the formats like bmp, jpg and so forth. Performance of the proposed system is better than existing system